2014
DOI: 10.1007/s10453-014-9327-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein expression of Platanus pollen following exposure to gaseous pollutants and vehicle exhaust particles

Abstract: Being major ornamental street trees, species of Platanus are widely planted in the Shanghai urban area. A great deal of allergenic Platanus pollen is released from the trees and suspended in the atmosphere during its flowering season, ultimately causing allergic respiratory diseases. Few papers have focused on the distribution of this type of pollen and its expression of allergenic proteins. In order to investigate any differences in protein expression in Platanus pollen following exposure to gaseous and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…This can cause severe pollinosis (Lu et al 2012) and has been reported to aggravate breathing difficulties in asthma patients (Subiza et al 1994;Varela et al 1997). The leaf structure, pest control, pollen, and cold resistance of P. acerifolia have all been reported (Li et al 2007;Lu et al 2012Lu et al , 2014Mimet et al 2009;Zhang et al 2011). Genetic engineering approaches have focused on breeding nonflowering or fruitless varieties through overexpressing a flowering repressor gene (Jensen CS 2004).…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 98%
See 1 more Smart Citation
“…This can cause severe pollinosis (Lu et al 2012) and has been reported to aggravate breathing difficulties in asthma patients (Subiza et al 1994;Varela et al 1997). The leaf structure, pest control, pollen, and cold resistance of P. acerifolia have all been reported (Li et al 2007;Lu et al 2012Lu et al , 2014Mimet et al 2009;Zhang et al 2011). Genetic engineering approaches have focused on breeding nonflowering or fruitless varieties through overexpressing a flowering repressor gene (Jensen CS 2004).…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 98%
“…Platanus acerifolia (London plane tree) is a hybrid of Platanus occidentalis and Platanus orientalis (Li et al 2007;Lu et al 2012Lu et al , 2014Mimet et al 2009;Zhang et al 2011) and is an avenue tree in temperate and subtropical regions (Lu et al 2012). P. acerifolia has many desirable characteristics, such as root compaction, rapid growth, and tolerance to pruning and atmospheric pollution (Li et al 2007;Zhang et al 2011).…”
Section: Responsible Editor: Philippe Garriguesmentioning
confidence: 99%
“…Most studies of this phenomenon were conducted on the protein Bet v 1, birch pollen, and it was confirmed, on molecular level, as a posttranslational modification of this protein by NO 2 [25]. In a polluted environment, higher allergenicity and changes in the protein composition of the pollen of Platanus orientalis was noted, one of the most important species in urban forestry of the warmer area of the world [26]. Also, pollen of invasive weed Artemisia artemisiifolia is more potent in allergenicity at elevated levels of NO 2 [27].…”
Section: Gaseous Pollutantsmentioning
confidence: 88%
“…Dominant pollutants are nitrogen, sulfur and carbon oxides, ozone, and PM10 (Wang et al 2008). Many authors claimed that air pollution affects the decrease in pollen viability and production; pollen grains may be smaller, often deformed or crashed (Majd et al 2004; Rezanejad 2009; Lu et al 2014; Sénéchal et al 2015; Kaur et al 2015). Chemical pollution may influence the biochemical composition of pollen.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Majd et al (2004) detected a decrease of protein content in pollen. Consequently, chemical air pollutants may alter the allergenic potency of pollen by inducing substantial molecular changes of proteins, consisting in their nitration and oxidation (Alscher et al 1997; Bryce et al 2010; Karle et al 2012; Ackaert et al 2014; Lu et al 2014). Guedes et al (2009) stated differences in protein profiles in pollen sampled from polluted sites.…”
Section: Introductionmentioning
confidence: 99%